Sejarah Masa Kemajuan Islam Pada Masa Bani Umayyah - Andriani Marshanda Lubis; Ririn Marheni Br Barus; Muhammad Basri (BADAN PENERBIT STIEPARI PRESS, 2023)
The Umayyad Dynasty was a dynasty based in Damascus which was formed after the end of the Shiffin field. The Umayyad Daulah was founded by someone named Muawiyah Bin Abi Sufyan and originated in 41H/661M. He was governor during the reign of Umar bin Khattab and Usman Bin Affan. When he was still governor, he was already a military reserve which would allow him to maintain his position in the future. This includes the time when he was governor of the Umayyads, where his greatest contribution was in the fields of politics and government. This method uses a method library approach. This article aims to explain the history of the Umayyad Dynasty, starting from the period in which the Umayyad Dynasty was formed, ending with the period of progress and ending with the period of decline of the Umayyad Dynasty, so that everyone, including scholars, can understand and increase knowledge about the history of the Umayyá dynasty from formation time to the end. The method used is called bibliography, and refers to several conceptual summaries.